2007
DOI: 10.1111/j.1095-8649.2007.01437.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of egg predation and physical disturbance on lake trout Salvelinus namaycush egg mortality and implications for life‐history theory

Abstract: The influence of egg predators and physical disturbance on lake trout Salvelinus namaycush egg mortality was investigated in situ in Lake Michigan where recruitment is below detectable levels and egg predator abundance is high. Comparisons were made with Lake Champlain where recruitment is low and egg predator abundance is also low and with Parry Sound (Lake Huron) where recruitment is moderate and egg predators are in low abundance. A multi-density egg seeding method (100 to 5000 eggs m À2 ) was used to quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…These characteristics will provide uniform and less variable sizes of interstitial space thereby limiting access by interstitial predators (e.g., rusty crayfish Orconectes rusticus, round goby Neogobius melanostomus, and sculpins Cottus spp.) which are often abundant on shallow, rocky habitats Jonas et al, 2005;Fitzsimons et al, 2007). For example, smaller substrate size reduced predation pressure on lake trout eggs by excluding larger mottled sculpins Cottus bairdi from interstitial spaces (Biga et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics will provide uniform and less variable sizes of interstitial space thereby limiting access by interstitial predators (e.g., rusty crayfish Orconectes rusticus, round goby Neogobius melanostomus, and sculpins Cottus spp.) which are often abundant on shallow, rocky habitats Jonas et al, 2005;Fitzsimons et al, 2007). For example, smaller substrate size reduced predation pressure on lake trout eggs by excluding larger mottled sculpins Cottus bairdi from interstitial spaces (Biga et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Empirical studies that have tracked the fate of incubating fish eggs have found that as many as 79-99% of eggs will succumb to some source of mortality before hatching (Johnson 1961;Rupp 1965;Fitzsimons 1995;, and threats beyond predation can be prevalent. For example, benthic eggs can be subjected to disturbance by winddriven currents that may cause them to be buried under shifting sediments (Fitzsimons 1995;Fitzsimons et al 2007), and cool water temperatures can extend incubation and possibly increase the risk of mortality (e.g., Rice et al 1987b). In the hypolimnetic waters of Lake Michigan where bloater eggs are incubating and temperatures are relatively stable yet cold, we suspect that predation would be the primary source of egg mortality, although disturbance by currents remains a possibility (Gottlieb et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…However, at high current velocities and energy fluxes that can be caused by storms or by ships passing close to a spawning site, waves may also depress egg survival at sites with clean spawning substratum. Highintensity waves have already been shown to be an important habitat factor influencing egg survival of shallow water spawning fish (Rupp 1965;Fitzsimons et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…The egg stage is a critical bottleneck for many fish species, and egg survival is a major factor affecting year class strength (Gafny et al 1992;Fitzsimons et al 2007;Probst et al 2009). Knowledge about biotic and abiotic factors mediating egg survival, therefore, is important for the management of fish stocks and fish population modelling.…”
Section: Introductionmentioning
confidence: 99%